A Legal Review of the Implementation of a One-Semester Marriage Guidance Course for Prospective Brides and Grooms at the District/City Ministry of Religion, Religious Affairs Offices - Ahmad Nafhani; Yulianiva Maulida (al-Afkar, Journal For Islamic Studies, 2025)
This paper is based on the pattern of Minister Nasaruddin Umar's initiative to implement a one-semester premarital course aimed at reducing divorce rates, specifically noting that a large percentage of marriages (35%) end in divorce, especially among couples married less than five years. The minister identified economic hardship, the age gap, educational disparities, and interfaith marriages as the main factors leading to divorce. The legal framework prescribes programs prioritizing gender equality and well-being, seeking to address the social challenges posed by divorce and improving marital harmony through structured educational initiatives. The discourse identifies the importance of statistical data in shaping effective policies and programs while emphasizing collaborative efforts between various government ministries to improve household quality and resilience. This analysis uses a Normative Juridical approach, which emphasizes the inventory of positive law, legal doctrine, and historical legal studies, with a focus on regulatory frameworks such as the Minister of Religious Affairs Decree and Law No. 1/2019 on Marriage.